2019
DOI: 10.1111/raq.12331
|View full text |Cite
|
Sign up to set email alerts
|

A systematic literature review of the major factors causing yield gap by affecting growth, feed conversion ratio and survival in Nile tilapia (Oreochromis niloticus)

Abstract: Productivity among small‐ and medium‐scale tilapia farms varies considerably. The difference between the best performers and lower ones (yield gap), is affected by differences in growth rate and feed conversion ratio (FCR). FCR at the farm level is strongly influenced by survival of fish. In this study a systematic literature review of two databases (ASFA and CAB‐Abstracts) identified 1973 potentially relevant articles. Data from 32 articles that met the inclusion criteria were analysed using linear mixed mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
38
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(43 citation statements)
references
References 65 publications
3
38
0
2
Order By: Relevance
“…Meta‐analysis studies with cattle, sheep, pig and goat also revealed moderately higher heritability estimates of growth traits (Akanno, Schenkel, Quinton, Friendship, & Robinson, 2013; Jembere et al., 2017; Safari, Fogarty, & Gilmour, 2005). Most of the aquaculture species are raised in the diverse water environments characterized by highly variable aquatic parameters among different ponds or production units, for example variation in temperature, salinity, pH and level of dissolved oxygen, which might greatly affect overall animal production (Mengistu, Mulder, Benzie, & Komen, 2019). Moreover, due to ease in transportation of fertilized eggs and larvae, aquaculture species are disseminated across many locations and experience great variability in rearing conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Meta‐analysis studies with cattle, sheep, pig and goat also revealed moderately higher heritability estimates of growth traits (Akanno, Schenkel, Quinton, Friendship, & Robinson, 2013; Jembere et al., 2017; Safari, Fogarty, & Gilmour, 2005). Most of the aquaculture species are raised in the diverse water environments characterized by highly variable aquatic parameters among different ponds or production units, for example variation in temperature, salinity, pH and level of dissolved oxygen, which might greatly affect overall animal production (Mengistu, Mulder, Benzie, & Komen, 2019). Moreover, due to ease in transportation of fertilized eggs and larvae, aquaculture species are disseminated across many locations and experience great variability in rearing conditions.…”
Section: Discussionmentioning
confidence: 99%
“…At the end of the second period (day 100), FCR of Group A (23 to 17 °C) increased while FCR of Group B (17 to 23 °C) decreased, although the differences in FCR between the two groups at day 100 were not statistically significant. The temperature for best feed consumption in many species, such as Nile tilapia ( Oreochromis niloticus ), hapuku ( Polyprionoxygeneios ), and others, is slightly higher than the one for best growth, and the temperature for best FCR is lower that the temperatures for best feed consumption and growth [ 44 , 45 , 46 ] This is in line with our results, as we found higher feed consumption and SGR in Group B (17–23 °C) without an associated improvement in FCR at the end of the trial (day 100).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the mortality considered here refers to the total percentage recorded over the grow-out cycle, i.e., historical mortality. Rates of mortality vary considerably depending on the production stage and farm management adequacy, with 20-71% mortality reported for tilapia, and is an important tool for the identification of critical welfare points identification (40). However, in addition to the lack of this indicator usually observed on small farms, a low mortality rate does not guarantee the absence of disease (26) or a high degree of welfare (5).…”
Section: Discussionmentioning
confidence: 99%
“…The economic demand for a short production cycle and fast growth rate was likely related to the high protein levels in the fish diet. However, Mengistu et al (40) showed that tilapia FCR decreased with increasing CP, DO, and pH. Thus, this management may negatively affect fish FCR and their weight gain.…”
Section: Discussionmentioning
confidence: 99%